The system approach to estimating the efficiency of the management personnel activity - Vlasova, Tatiana (Marketing & Menedzsment, 2019)
The aim of this study is to describe the methodological foundations of the systems approach to performing the integrated analysis of the management activity efficiency, the description and justification of the 3-level “pyramidal” model, which will include the indicators of the management personnel efficiency according to 3 levels, in particular, of individual managers, the whole management system and its top management; also in this research the author will form a set of the efficiency indicators of the management personnel activity, will develop the normative dynamic model for estimating the management activity efficiency and will present the recommendations on the application of the obtained model as an etalon arrangement of the indicators.